A technique for improving text editing on touchscreen devices. (August 2018) - Costagliola, Gennaro; De Rosa, Mattia; Fuccella, Vittorio
Abstract: We present a gesture-based technique for the efficient text editing on touchscreen devices. In order to define our technique, we ran a preliminary experiment and detected the most natural gestures that users choose when unconstrained. Users can perform the main operations such as select, move, copy, delete and paste directly on the text, thus making the editing technique independent from the text entry method (e.g. a soft keyboard). As an evaluation, we compared our gestural editing technique to the one available on most Android devices. The experimental results show that the gestural editing technique is more efficient when the text font size increases.